Interactive Effect of FYM and Inorganic Fertilizers on Performance of Tomato (Lycopersicon esculentum Mill) - S Manohar, S V; Paliwal, R (Annals of Arid Zone, 2016)
The present field experiment was conducted during summer season of 2010 at the Horticulture farm, SKN College of Agriculture, Jobner (Rajasthan) to study the interactive effect of farm yard manur (FYM) and inorganic fertilizers on performance of tomato (Lycopersicon esculentum Mill). The experiment consisted of four levels of FYM (control, 10, 15 and 20 t ha-1) and four combinations of inorganic fertilizers (control, 50% RDF + B + Zn, 75% RDF + B + Zn and 100% RDF + B + Zn), in factorial randomized block design with three replications. Results indicated that the combined use of FYM @ 15 t ha-1 and 75% RDF + B + Zn proved to be the best treatment combination in terms of number of primary branches per plant, average number of fruits per plant, fruit yield, net returns and B:C ratio of tomato. This combination produced 372.97 q ha-1 fruit yield along with net returns of Rs. 178452 ha-1 and B:C ratio of 3.94.